2020
DOI: 10.1038/s41467-020-16838-w
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activation using anti-idiotypic masks enables tumor specificity of a folate receptor 1-T cell bispecific antibody

Abstract: T-cell bispecific antibodies (TCBs) crosslink tumor and T-cells to induce tumor cell killing. While TCBs are very potent, on-target off-tumor toxicity remains a challenge when selecting targets. Here, we describe a protease-activated anti-folate receptor 1 TCB (Prot-FOLR1-TCB) equipped with an anti-idiotypic anti-CD3 mask connected to the anti-CD3 Fab through a tumor protease-cleavable linker. The potency of this Prot-FOLR1-TCB is recovered following protease-cleavage of the linker releasing the anti-idiotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 58 publications
1
51
0
Order By: Relevance
“…Geiger et al, recently demonstrated an elegant way to further elevate tumor specificity in the 2 + 1 format by fusing an anti-idiotypic scFv masking the CD3 binding Fab. Only after tumor-associated proteolytic cleavage of the linker, the CD3-specific Fab is unmasked and able to engage T cells, resulting in an elevated safety profile ( 97 ). A second possible engineering strategy to further elevate tumor specificity is to incorporate tumor-specific antigen binding.…”
Section: Discussionmentioning
confidence: 99%
“…Geiger et al, recently demonstrated an elegant way to further elevate tumor specificity in the 2 + 1 format by fusing an anti-idiotypic scFv masking the CD3 binding Fab. Only after tumor-associated proteolytic cleavage of the linker, the CD3-specific Fab is unmasked and able to engage T cells, resulting in an elevated safety profile ( 97 ). A second possible engineering strategy to further elevate tumor specificity is to incorporate tumor-specific antigen binding.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on a T-cell bispecific antibody generated to bring Folate Receptor 1 (FOLR1) expressing tumor cells in close proximity to CD3 expressing cytotoxic T-cells (Fig. S1A) (26). FOLR1 is overexpressed in many solid, epithelial-derived tumors including ovarian, lung and breast cancer(27), but is also expressed to a lower degree on normal epithelial cells as found in the lung and kidneys (28).…”
Section: Resultsmentioning
confidence: 99%
“…In light of the toxicity risk predicted above, and hoping to define a potential therapeutic window of FOLR1(Hi) TCB, we performed the same study with chips seeded with the high FOLR1 expressing ovarian carcinoma cell line, HeLa, previously used to assess drug efficacy(26). Although no effects were seen at the lowest concentration, all concentrations starting from 2 ng/mL induced significant T-cell activation (measured at 48 hours), cancer cell apoptosis (from 24 hours onwards) and strong cytokine release, as expected from the high level of FOLR1 expression in HeLa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another compelling route for locoregional immunomodulation has been the strategic use of protein engineering to develop immunostimulatory drugs that are either retained or activated in the tumor microenvironment (54)(55)(56)(57). These sophisticated strategies have clearly demonstrated the power of local immunostimulation and can achieve impressive therapeutic results with minimal toxicity.…”
Section: Discussionmentioning
confidence: 99%